Study on building information modeling (BIM) process flow in construction industry: a model exploratory approach to research - Nurulashikin, Daud (2014)
BIM is a technology that uses parametric • modeling to minimize the time spent in coordination of design details like locating and moving architectural elements and the corresponding required documentation changes. It also has the added benefit of allowing the entirety of design development to occur in three dimensions possibly leading to better quality designs and enabling timely creation of realistic renderings. It allows greater control of document information, such as schedules, and can produce and manage information like occupancy plans for use in the long term facility management process. Currently, the facility delivery process remains fragmented and it depend on paper-based modes of communication. Errors and omissions in paper documents often cause unanticipated field costs, delays and eventual lawsuits between the various parties in a project team. In using CAD, we are essentially drawing the same way we did on paper - in two dimensions. The only difference is that now the drawings are electronic and easier to manipulate and reproduce. We can move entire walls with a few clicks of the mouse where as on paper the entire sheet had to be redrawn. This drastically speeds up the process but also creates some challenges as well. One of the common problems associated with 2D- based communication during the design phase is the considerable time and expense required to generate critical assessment information about a proposed design, including cost estimates, energy use analysis, and structural details. So BIM is the new thing can solve these problems. The Objectives of this study are to explore, appraise and synthesize relevant literature with specific focus on BIM's process flow and develop 3D parametric model, to test the BIM's process flow and develop 3D parametric model using Revit Software. The 3D parametric model helps different parties to better understand the style, especially details of the design. 3D parametric modeling facilitates the design of substantial and intricate models with 3D however impose a mode of modeling and also planning. The ability to extract geometric and also property information from a building model easy use in design, investigation, construction planning or with operations. Using walkthrough tool, it allow visualizing inside the building and it helps to check error inside the building. So with these 3D parametric modeling hopes it can help to solve problems before and during the early phases of design and save time of the project.